The role of value orientations and media attention in predicting the personal norm and public intention to consume produce of urban farms - Goh, Tong Jee (2024)
In a bid to strengthen food security, cities are embracing urban farming to produce food. It is believed that urban farming is a sustainable means of cultivating crops for urban populations. Urban farms are equipped with advanced technology to optimize crop yield. Meanwhile, multiple media contents have reviewed the risks and benefits of urban farming for consumers. Applying an extended norm-activation model, this study examined how the relationships among technological optimism, biospheric values, attention to media content on the risks and benefits of urban farming, and the norm-activation constructs predict the intention to consume the produce of urban farms. Results of a cross-sectional survey conducted in Singapore (N = 1209) showed that technological optimism and biospheric values influenced attention to media content. These variables in turn influenced personal norms and intention to consume through the norm-activation constructs.